Evaluation of rest interval following a series of tuck jumps on anaerobic performance - Christopher J. Cleary; Summer B. Cook; Ashley A. Herda (Journal of Exercise Science & Fitness)
Background/objective: This study assessed the influence of rest interval duration after tuck jumps on 10-s Wingate outcomes and countermovement jump height. Methods: Eighteen resistance trained individuals (males: n = 10, 21.3 ± 3.6 years; females: n = 8, 22.1 ± 2.2 years) volunteered to participate in four sessions: familiarization, 3-min rest interval with no jumps (CON), and two randomized experimental sessions with a rest interval of either 1-min (ER1) or 5-min (ER5) after a series of tuck jumps. Countermovement jump (CMJ) height was assessed at baseline (PRE) and after (POST) the CON, ER1, and ER5 conditions, and 10-s Wingate cycling testing. Wingate relative peak power (RPP) and mean peak power (RMP) were measured. Separate mixed-factorial repeated measures analyses of variance assessed changes across conditions and sex for the Wingate variables and conditions, sex, and time for CMJ height at an alpha of p ≤ 0.05. Results: RPP and RMP were significantly greater than CON for ER1 by 0.92 ± 0.23 W kg−1 and 0.41 ± 0.14 W kg−1, respectively, and ER5 by 0.77 ± 0.23 W kg−1 and 0.36 ± 0.10 W kg−1, respectively. ER1 and ER5 RPP and RMP were similar (p > 0.05). For CMJ height, there was only a main effect for sex as males jumped higher than females by 31.3 % (p = 0.002). Conclusion: Performing tuck jumps prior to anaerobic exercise may increase performance for up to 5-min.